Pengaruh Kompetensi terhadap Kinerja (Studi Empiris pada Peternak Sapi Perah Binaan Koperasi Peternak Sapi Bandung Utara (KPSBU)) - Yustian, Okky Rizkia (Jurnal Aplikasi Manajemen, 2015)
The purpose of this study was to determine how competence dairy farmers affect theperformance of the breeder partially and simultaneously. This study was a descriptive studyof verification that aims to describe the state of the population competence or empirical factsand measure the influence between variables. Variable competence consists of three indicators,namely; knowledge, skills and abilities. The higher the knowledge, skills and abilities,mean that the higher the performance of dairy farmers. Data processing is done with the helpof Exel and SPSS. software Analysis of data using inferential statistical analysis to determinethe influence of some independent variable (X) to the dependent variable (Y) either partiallyor simultaneously. Results from this study showed that the variable competence consists ofknowledge, skills and abilities have a significant influence on the performance simultaneouslyand partially, the variable has the knowledge of the most dominant influence on theperformance of dairy farmers.